ANALISIS PERKEMBANGAN DAN KESESUAIAN LAHAN PERMUKIMAN TERHADAP RTRW KOTA PADANG PANJANG - Yashinta Dewi; Deded Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objectives of this study are 1) To analyze the dynamics of residential land development in Padang Panjang City in the 2015-2024 period, 2) To evaluate the suitability of existing residential land in 2024 with the applicable Regional Spatial Plan (RTRW). This study uses a descriptive quantitative method with a spatial analysis approach. This study integrates descriptive statistics and spatial analysis to map and analyze geographic data. In this study, descriptive analysis is used to describe the data, while spatial analysis is used to map and analyze land development and then identify its suitability for residential land based on spatial patterns. The results show that the area of ​​settlement in Padang Panjang City experienced a significant increase of 134.42 Ha from 520.02 Ha in 2015 to 654.44 Ha in 2024, along with a decrease in the area of ​​forest/dense vegetation and rice fields/fields. The land cover classification accuracy test reached 94% Kappa Coefficient for both years, confirming the reliability of the data. However, an evaluation of residential land suitability with the Padang Panjang City Spatial Plan (RTRW) for 2012-2032 revealed serious deviations, with 101.67 hectares of residential land not in accordance with its intended use, occupying riverbanks, plantations, rice fields, green open spaces (RTH), and landslide-prone areas. These deviations are spread across all sub-districts, with the highest percentages in Silaing Bawah, Kampung Manggis, and Koto Panjang.